2016
DOI: 10.1016/j.jpha.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Liquid chromatography--tandem mass spectrometry method for simultaneous determination of albendazole and albendazole sulfoxide in human plasma for bioequivalence studies

Abstract: An improved high performance liquid chromatography--tandem mass spectrometry (LC–MS/MS) method has been developed for sensitive and rapid determination of albendazole (ABZ) and its active metabolite, albendazole sulfoxide (ABZSO), in the positive ionization mode. The method utilized solid phase extraction (SPE) for sample preparation of the analytes and their deuterated internal standards (ISs) from 100 µL human plasma. The chromatography was carried out on Hypurity C18 column using acetonitrile-2.0 mM ammoniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…Based on the published data, SRM scans were performed for 266. (5,7). Fragment-specific mass spectrometer parameters were evaluated by direct infusion of 1 g/ml albendazole, albendazole sulfoxide, and albendazole sulfone dissolved in methanol to the mass spectrometer, followed by a stepwise optimization of source parameters (see Table S2 in the supplemental material).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the published data, SRM scans were performed for 266. (5,7). Fragment-specific mass spectrometer parameters were evaluated by direct infusion of 1 g/ml albendazole, albendazole sulfoxide, and albendazole sulfone dissolved in methanol to the mass spectrometer, followed by a stepwise optimization of source parameters (see Table S2 in the supplemental material).…”
Section: Resultsmentioning
confidence: 99%
“…Ascaris lumbricoides, hookworms, and Trichuris trichiura. In addition, pharmacokinetic (PK) studies have been mostly performed in healthy adults and in a few cases in adults infected with Wuchereria bancrofti or hydatid disease (4)(5)(6)(7)(8)(9)(10)(11). Only three small PK studies have been performed with 5 to 10 children who received albendazole treatment and who were infected with hydatid disease, neurocysticercosis, or Giardia intestinalis (12)(13)(14).…”
mentioning
confidence: 99%
“…Albendazole is only detectable for a short time in plasma due to its rapid conversion to its major active metabolites such as ABZ-sulfoxide (ABZ-OX) and ABZ-sulfone (ABZ-ON) and subsequently low drug concentrations [ 6 ]. Various bioanalytical methods are available for analysis of ABZ and its metabolites in different biological matrices [ [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] ]. Wojnicz et al reported a LC–MS/MS method for the quantitation of ABZ and ABZ-OX in 200 μL plasma with a LLOQ of 5 and 10 ng/mL)[ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The method to extract the drug and its metabolite was based on our previous study with some modification (Rathod et al, ). To an aliquot of 500 μL of spiked plasma samples (calibration standards and QC), 100 μL of 500 μg/mL working solution of phenacetin was added and vortexed for 10 s. Further, 100 μL of 5 m m ammonium acetate solution in water was added, vortexed for another 1.0 min and centrifuged at 13,148 g for 5 min at 10°C.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, several methods are described for the determination of ABZSO and/or other inactive metabolites of ABZ in human serum (Mirfazaelian, Dadashzadeh, & Rouini, ), bovine plasma (Belaz, Cass, & Oliveira, ), human cancer cell lines (Belaz et al, ), dog plasma (Khalil, El‐karbane, Azougagh, El‐harti, & Taoufik, ), human plasma (González‐Hernández, Ruiz‐Olmedo, Cárdenas, & Jung‐Cook, ; Saraner et al, ) and cerebrospinal fluid (González‐Hernández et al, ). Simultaneous analysis of ABZ and ABZSO is also reported in different biological matrices using HPLC (Kitzman, Cheng, & Fleckenstein, ), LC–MS/MS (Rathod et al, ; Wojnicz et al, ) and UPLC–MS/MS (Shen et al, ; Zhang et al, ). Few other methods describe simultaneous estimation of ABZ with other anthelmintic agents like closantel (Phatak, Vaidya, & Phatak, ), thiabendazole (Su, Chang, Chang, & Chou, ), mebendazole (Su et al, ), ivermectin (Patel, Joshi, & Patel, ; Waldia, Gupta, Issarani, & Nagori, ) and praziquantel (Gandla, Lalitha, Bommakanti, Suthakaran, & Pallavi, ; Shah, Dey, Pradhan, Jain, & Upadhyaya, ).…”
Section: Introductionmentioning
confidence: 97%